2014
DOI: 10.1155/2014/747619
|View full text |Cite
|
Sign up to set email alerts
|

Will an Unsupervised Self-Testing Strategy Be Feasible to Operationalize in Canada? Results from a Pilot Study in Students of a Large Canadian University

Abstract: Background. A convenient, private, and accessible HIV self-testing strategy stands to complement facility-based conventional testing. Over-the-counter oral HIV self-tests are approved and available in the United States, but not yet in Canada. Canadian data on self-testing is nonexistent. We investigated the feasibility of offering an unsupervised self-testing strategy to Canadian students. Methods. Between September 2011 and May 2012, we recruited 145 students from a student health clinic of a large Canadian u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 22 publications
6
56
3
1
Order By: Relevance
“…Previous studies have largely reported that oral-fluid tests were appealing because they were easy to use, painless and did not require a blood sample [15,16,31]; although a study in Tanzania reported dislike for this method due to lack of familiarity [32]. Our study pointed to concerns by young people around accuracy of oral-fluid tests, a finding that has previously been cited in the United States [17,18].…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have largely reported that oral-fluid tests were appealing because they were easy to use, painless and did not require a blood sample [15,16,31]; although a study in Tanzania reported dislike for this method due to lack of familiarity [32]. Our study pointed to concerns by young people around accuracy of oral-fluid tests, a finding that has previously been cited in the United States [17,18].…”
Section: Discussionsupporting
confidence: 62%
“…These results are not discordant with the findings from a previous DCE study among long distance truck drivers in Kenya (Strauss, George, Lansdell, et al, 2018;, in which there was a slight (but not statistically significant) preference for nurse-administered testing. However, our results stand in contrast to a number of previously published studies' findings that self-testing was Figure 1: Stratified conditional logit models for sex and HIV testing history broadly preferred to clinic-based testing (Carballo-Diéguez, Frasca, Balan, Ibitoye, & Dolezal, 2012;Choko et al, 2015;Gaydos et al, 2011Gaydos et al, , 2013Kalibala et al, 2014;Kurth et al, 2016;Lippman et al, 2016;Marley et al, 2014;Nour et al, 2012;Pant Pai et al, 2014;Peck et al, 2014;Stevens, Vrana, Dlin, & Korte, 2018). This apparent contradiction may reflect the fact that by using the DCE, we were able to separate this attribute (self-testing versus nurse-administered testing) from other attributes that in practice are usually grouped together.…”
Section: Discussioncontrasting
confidence: 99%
“…They are from the communities and can easily reach pregnant women in remote settings. Our results clearly indicates towards the acceptance of pregnant women in rural settings for this test with uptake as 95%, which is higher than reported in other studies on oral fluid based rapid tests (83-85%) [20]. This concord with other studies conducted among rural women indicating for the preference of oral fluid-based tests over blood-based tests [21].…”
Section: Discussionsupporting
confidence: 72%